(untitled) (Eurasian Journal of Humanities and Social Sciences, 2022)
This article discusses the main methods of translating linguistic and cultural phraseological compounds into English and Uzbek. Phraseological expressions cannot be considered only as a separate part of linguistics, there are cases when they can be used or not, because they form an important part of the general vocabulary of English and Uzbek languages. Nowadays it is very important to follow the process of replenishment of the phraseological fund of English and Uzbek languages, because phrases appear very quickly and are inextricably linked with the development of science, new technologies, political games and the process of military conflict. It should be noted that phraseological compounds are common. Finding the phraseological connections in the source text and the appropriate equivalent in the translation process is the most important step for the translator